Usability Evaluation of SIDUMAS Badung Using Think Aloud, Heuristic Evaluation and SUS - Putra, I Nyoman Gede Ardi Yana; Candiasa, I Made; Dewi, Luh Joni Erawati (Sinkron : jurnal dan penelitian teknik informatika, 2023)
This study aims to 1) find out the problems that occur in the Badung Regency community complaint system (SIDUMAS) by conducting a usability evaluation using the think-aloud method, heuristic evaluation and system usability scale, 2) conduct a usability evaluation on the community complaint system can determine the level of application usability and determine recommendations for improvements needed by the Badung community complaint system (SIDUMAS). Respondents who participated in this study were Badung people consisting of 5 usability experts and 30 general public. Determination of respondents in this study based on the criteria of the method used. The data in this study were obtained through usability evaluation results on the public complaint application questionnaires and data from interviews with respondents. The method used to evaluate the public complaint system is a combination of 3 methods, namely think aloud, heuristic evaluation and system usability scale which will produce an assessment to determine the usability and recommendations for improvements to the Badung SIDUMAS system. The results showed that: (1) Using the think-aloud method, it was found that the problems experienced by users of the community complaint system application on average experienced the same problems in the test. The results of research with heuristic evaluation found that there is 1 problem that has the highest severity rating where the problem must be fixed immediately. The results of the calculation of the average system usability scale score on user satisfaction obtained a score of 78 with acceptability ranges in the acceptable category. Furthermore, for the percentile rank score, the value obtained is 78 so it is in the grade B category. (2) Making recommendations for improvement in the study focused on changing the layout on the page and navigation menu on the results of data causing errors experienced by users.